UNCERTAINTY REGIMES AND RISKS IN MIGRATION AND THE SOCIO-CULTURAL SPECIFICITY OF DAGESTAN - Kapustina, Ekaterina Leonidovna (History, Archeology and Ethnography of the Caucasus, 2025)
The article proposes to consider the zones of uncertainty and risk in the lives of migrants from Dagestan using the example of long-term migration to the Arctic zone of Western Siberia. The focus will be on how migrants operate with various regimes of uncertainty and risk in migration precisely in the context of the socio-cultural specifics of the migrant-sending society. The article examines an example of the ambivalence of the uncertainty factor in the context of the translocal temporality of migrant life and the functioning of social networks. As a result of examining this migration case, several conclusions can be made. Firstly, it is worth recognizing that translocality as a theoretical scheme should not be perceived as a rigid impenetrable scheme and in the context of long-term migration, one way or another, a decrease in the competence of transmigrants regarding the socio-cultural and economic life of the sending region begins to occur, which increases the level of uncertainty in their translocal life. As a result, it is determined that not only life in the receiving society (a generally accepted point of view in migration studies) can become uncertain, but also in the sending one. Secondly, migrant social networks can not only reduce the feeling of uncertainty in a migrant, but also generate a zone of uncertainty that reduces his competence. Thirdly, translocal life in two worlds is always a challenge for a person's identity and the relationship between him and the basic elements of his life, which tend to double. This aspect of uncertainty was considered using the example of the perception of home by a translocal migrant from the north. In addition to the identified zones of uncertainty that appear in the situation of translocality, such a socio-cultural specificity of Dagestani society as the desire for risk was considered, which can be defined as a generally encouraged strategy of a daredevil. In this situation, migration as a risky undertaking can be perceived as a desired action for a male migrant.
Keywords: migration; uncertainty; risk; translocality; Western Siberia; Dagestan